A high-strength recycled aggregate concrete and its preparation process
By adding reinforcing fibers to the concrete and coating liquid on the surface of the steel fibers to form a rough pore structure, the problem of insufficient mechanical strength of existing recycled aggregate concrete is solved, and the high strength and compressive strength of concrete is improved.
Patent Information
- Application Number
- CN202310579040.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-22
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-05-22
AI Technical Summary
The mechanical strength of existing recycled aggregate concrete needs to be improved.
By adding reinforcement fibers to the concrete and coating the surface of the steel fibers, a coating layer is formed after drying, and the corrosion of the steel fibers is reduced, and a rough pore structure is formed on the surface of the coating layer through the acetone solution to enhance the fixity between the fibers and the concrete.
The stability of the fixation of reinforcing fibers in concrete is improved, the mechanical strength enhancement effect of reinforcing fibers on concrete is improved, and the compressive strength of concrete is improved.
Abstract
Description
Technical Field
[0001] The invention relates to the field of concrete preparation, and in particular to a high-strength recycled aggregate concrete and a preparation process thereof. Background Art
[0002] Due to the continuous development of today's society, the construction industry has entered a stage of rapid development, and the demand for concrete is increasing. At present, concrete aggregates are mainly natural rocks and gravel, which are non-renewable resources. At the same time, the mining process will cause a lot of environmental pollution and accelerate the depletion of natural rock and gravel resources. Therefore, it is urgent to find substitutes to alleviate the consumption of natural resources; waste concrete, as a kind of construction waste, has a huge annual output and is usually treated by open-air stacking and landfill, which can easily cause environmental pollution. By crushing, cleaning and grading the concrete waste, it can be used as recycled aggregate and mixed with other raw materials to form new concrete, also called recycled aggregate concrete. In this way, the waste concrete can be reused, reducing environmental pollution while meeting the country's strategic goal of sustainable development. Therefore, it is widely favored by researchers.
[0003] In the above-mentioned related technologies, the inventors believe that the mechanical strength of existing recycled aggregate concrete during use needs to be improved. Summary of the invention
[0004] In order to improve the mechanical strength of recycled aggregate concrete, the present application provides a high-strength recycled aggregate concrete and a preparation process thereof.
[0005] In the first aspect, the present application provides a high-strength recycled aggregate concrete, which adopts the following technical solution:
[0006] A high-strength recycled aggregate concrete mainly comprises the following raw materials in parts by weight: 70-100 parts of cement, 50-60 parts of recycled coarse aggregate, 30-50 parts of recycled fine aggregate, 20-30 parts of fly ash, 80-130 parts of water, 10-20 parts of reinforcing fiber, and 2-3 parts of water reducing agent; the preparation method of the reinforcing fiber comprises the following steps:
[0007] S11: heating and melting polyamide 66 and polymethacrylate and mixing them with calcium chloride to obtain a coating liquid, applying the coating liquid on the surface of the steel fiber, and drying to obtain a pretreated fiber;
[0008] S12: The pretreated fiber prepared in step S11 is immersed in an acetone solution, and then taken out and dried.
[0009] By adopting the above technical scheme, the above raw materials are mixed and prepared into concrete, and the addition of reinforcing fibers has a good reinforcing effect on the concrete. In the preparation process of the reinforcing fibers, after the steel fibers are directly added to the concrete, during the curing and use of the concrete, the surface of the steel fibers is easily corroded under the hydration of cement, which affects the reinforcing effect of the steel fibers on the mechanical properties of the concrete. By arranging a coating liquid on the surface of the steel fibers, the coating liquid forms a coating layer to wrap the steel fibers after drying, thereby reducing the corrosion of the steel fibers when mixed with other raw materials. At the same time, since both polymethacrylate and calcium chloride are soluble in acetone, by immersing the pretreated fibers in an acetone solution, under the dissolving action of acetone, the pretreated fibers are The polymethacrylate on the surface of the treated fiber is dissolved, making the surface of the pretreated fiber rough, thereby improving the stability of the prepared reinforcing fiber fixed in the concrete; when the coating liquid is dried and coated on the surface of the steel fiber, calcium chloride is embedded in the surface of the coating layer, and the calcium chloride is dissolved by the dissolving action of the acetone solution to form pores on the surface of the coating layer. When the reinforcing fiber is mixed with other raw materials of the concrete, the gel formed by the hydration of the cement will fill in the pores. During the drying process of the concrete, a "rivet" structure is formed on the surface of the reinforcing fiber, so that the reinforcing fiber can be more firmly connected to the concrete, and it is not easy to detach from the concrete when the concrete is subjected to external force, thereby further improving the reinforcing effect of the reinforcing fiber on the mechanical strength of the concrete.
[0010] Optionally, when the pretreated fiber is immersed in the acetone solution, the acetone solution is simultaneously subjected to ultrasonic treatment.
[0011] By adopting the above technical solution, the pretreated fiber is immersed in an acetone solution. During the dissolution process of calcium chloride, calcium chloride is easily blocked in the pores, resulting in a limited contact area between calcium chloride and the acetone solution, which affects the dissolution rate of calcium chloride. Through the oscillation effect of ultrasonic treatment, calcium chloride can be separated from the surface of the reinforcing fiber as soon as possible, thereby increasing the dissolution rate of calcium chloride and improving the preparation rate of the reinforcing fiber.
[0012] Optionally, the steel fiber in step S11 is immersed in a zinc phosphate solution before use, and then taken out and dried.
[0013] By adopting the above technical solution, the steel fiber is immersed in a zinc phosphate solution, so that the zinc phosphate is deposited on the surface of the steel fiber to form a protective film, which further prevents the steel fiber from contacting with oxygen and moisture, slows down the corrosion rate of the steel fiber in the concrete, and improves the service life of the prepared reinforcing fiber. At the same time, the reinforcing effect of the reinforcing fiber on the mechanical properties of the concrete is also improved.
[0014] Optionally, the steel fibers are composed of long fibers and short fibers in a mass ratio of (3-5):(2-3); the length of the long fibers is 35-45 mm, and the length of the short fibers is 15-25 mm.
[0015] By adopting the above technical solution, long fibers and short fibers are combined. The long fibers can play a good traction role and enhance the toughness of concrete. However, during the mixing process, the long fibers are prone to cross-clustering, which reduces their dispersion and has limited reinforcing effect on the concrete. The short fibers can play a good filling role and connect micro cracks, but the effect of short fibers on enhancing the mechanical properties of concrete is limited. Through the combination of long fibers and short fibers, the mechanical strength of the prepared concrete is further improved.
[0016] Optionally, the mass ratio of calcium chloride, polymethacrylate and polyamide 66 in step S11 is 1:(2-4):(13-18).
[0017] By adopting the above technical scheme, the mass ratio of calcium chloride, polymethacrylate and polyamide 66 is adjusted. When the content of calcium chloride and polymethacrylate is low, the pores formed on the surface of the reinforcing fiber are small, and the roughness of the surface of the reinforcing fiber is insufficient, so that the subsequent binding force of the prepared reinforcing fiber in concrete is insufficient, and the reinforcing fiber is easy to detach from the concrete when the concrete is subjected to external force, so that the reinforcing effect of the reinforcing fiber on the concrete is weakened; when the content of calcium chloride and polymethacrylate is excessive, the pores on the surface of the reinforcing fiber are excessive, so that other raw materials in the concrete are easy to contact with the steel fiber through the pores, causing corrosion to the steel fiber, and affecting the steel fiber The mechanical property enhancement effect of the concrete.
[0018] In a second aspect, the present application provides a process for preparing high-strength recycled aggregate concrete:
[0019] A preparation process of high-strength recycled aggregate concrete mainly comprises the following steps:
[0020] S1: Mix cement, recycled coarse aggregate, recycled fine aggregate, fly ash, reinforcing fiber and water reducing agent to prepare a premix; S2: Mix water and the premix, let it stand, and prepare a premixed mortar;
[0021] S3: solidify and cure the premixed mortar prepared in step S2.
[0022] By adopting the above technical scheme, cement, recycled coarse aggregate, recycled fine aggregate, fly ash, reinforcing fiber and water reducing agent are first mixed so that the reinforcing fiber can be evenly dispersed in each raw material to reduce the aggregation of the reinforcing fiber, and then mixed with water to hydrate the cement, so that the reinforcing fiber is fixed in the concrete, thereby improving the mechanical strength of the prepared concrete.
[0023] Optionally, before mixing the premix with water in step S2, a filler is added to the premix, and the filler is composed of at least one of styrene-butadiene rubber powder and glass fiber and a silane coupling agent in a mass ratio of (9-13):(0.2-0.3).
[0024] By adopting the above technical scheme, the styrene-butadiene rubber powder is mixed with the silane coupling agent, so that the methoxy groups in the styrene-butadiene rubber are hydrolyzed to produce silanol, and a film with functional groups is formed on the surface of the styrene-butadiene rubber, thereby improving the dispersibility of the styrene-butadiene rubber, so that after the styrene-butadiene rubber is added to the concrete, the styrene-butadiene rubber has a good filling and toughening effect on the concrete; after the glass fiber is mixed with the silane coupling agent, in the subsequent mixing process, the silane coupling agent combines with the hydroxyl groups on the surface of the glass fiber, and at the same time, due to the presence of a large number of amino groups, terminal carboxyl groups and amide bonds in polyamide 66, the silane coupling agent drives the chemical bonds on the surface of the glass fiber and the polyamide 66 to bond to form a composite, thereby making the internal structure of the prepared concrete denser and having better mechanical strength.
[0025] Optionally, the filler is composed of styrene-butadiene rubber powder, glass fiber and silane coupling agent in a mass ratio of (5-8):(4-5):(0.2-0.3).
[0026] By adopting the above technical scheme, styrene-butadiene rubber powder, glass fiber and silane coupling agent are mixed, and under the action of the silane coupling agent, the styrene-butadiene rubber powder and the glass fiber have good compatibility with other raw materials in concrete, and the toughness of concrete is improved through the filling effect of styrene-butadiene rubber powder, and the strength of concrete is improved through the filling effect of glass fiber. Under the joint action of the two, the mechanical strength of concrete is jointly improved.
[0027] Optionally, 5-8 parts of epoxy resin are added to the premixed mortar before curing.
[0028] By adopting the above technical solution, epoxy resin is added. During the mixing process, the epoxy resin can be cross-linked in the concrete to form a network structure. At the same time, the hydroxyl groups in the epoxy resin undergo a ring-opening reaction, and undergo physical adsorption and chemical bonding with the amino groups and amide bonds in polyamide 66, so that the reinforcing fibers are connected to the epoxy resin, and the reinforcing fibers are interspersed and fixed inside the network structure. Under the traction of the network structure, the migration of the reinforcing fibers during the concrete curing process can be reduced, thereby improving the reinforcing effect of the reinforcing fibers on the mechanical properties of the concrete.
[0029] In summary, this application has the following beneficial effects:
[0030] The present application adds reinforcing fibers into concrete, and in the process of preparing the reinforcing fibers, coats the surface of the steel fibers with a coating liquid, so that after the coating liquid dries, the steel fibers are protected and corrosion of the steel fibers is reduced; at the same time, polymethacrylate and calcium chloride in the coating liquid are dissolved by an acetone solution, so that a rough pore structure is formed on the surface of the coating layer; when the reinforcing fibers are added into the concrete, the cement can be interspersed in the pores after hydration to form a "rivet structure", thereby improving the fixing effect of the reinforcing fibers in the concrete, and thereby making the reinforcing fibers have a good mechanical property enhancement effect on the concrete. DETAILED DESCRIPTION
[0031] The present application is further described in detail below with reference to the embodiments and comparative examples;
[0032] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available.
[0033] Preparation Example
[0034] Reinforced fiber preparation example 1
[0035] The preparation method of the reinforcing fiber in this preparation example comprises the following steps:
[0036] S11: Take a reaction bottle, add polyamide 66 and polymethacrylate into the reaction bottle, heat the reaction bottle at 280°C to melt polyamide 66 and polymethacrylate, then add calcium chloride into the reaction bottle, mix evenly to prepare a coating liquid; apply the coating liquid on the surface of the steel fiber, and after drying, prepare the pretreated fiber; the mass ratio of calcium chloride, polymethacrylate and polyamide 66 used is 1:2:13; the steel fiber used is short fiber, and the length of the short fiber is 20 mm; S12: Take an impregnation bucket, add acetone solution into the impregnation bucket, place the pretreated fiber in the acetone solution and immerse it for 20 minutes, take it out and dry it; the mass fraction of acetone in the acetone solution used is 50%.
[0037] Reinforced fiber preparation example 2
[0038] The difference between this reinforcing fiber preparation example and the reinforcing fiber preparation example 1 is that the mass ratio of calcium chloride, polymethacrylate and polyamide 66 used in step S11 is 1:4:18; the steel fiber used is a long fiber with a length of 40 mm.
[0039] Reinforced fiber preparation example 3
[0040] The difference between this reinforcing fiber preparation example and the reinforcing fiber preparation example 1 is that the mass ratio of calcium chloride, polymethacrylate and polyamide 66 used in step S11 is 1:3:15; the steel fiber used is composed of long fibers and short fibers in a mass ratio of 4:2.5; the length of the long fibers used is 40 mm, and the length of the short fibers is 20 mm.
[0041] Reinforced fiber preparation example 4
[0042] The difference between this reinforced fiber preparation example and reinforced fiber preparation example 3 is that in step S12, when the pretreated fiber prepared in step S11 is immersed in the acetone solution, the acetone solution is ultrasonically treated at a power of 600W.
[0043] Reinforced fiber preparation example 5
[0044] The difference between this reinforcing fiber preparation example and reinforcing fiber preparation example 4 is that the steel fiber used in step S11 is immersed in a zinc phosphate solution for 10 minutes before use, and then taken out and dried; the mass concentration of zinc sulfate in the zinc sulfate solution used is 30%.
[0045] Example
[0046] Example 1
[0047] The high-strength recycled aggregate concrete in this embodiment mainly includes the following raw materials by weight: 70 kg of cement, 50 kg of recycled coarse aggregate, 30 kg of recycled fine aggregate, 20 kg of fly ash, 80 kg of water, 10 kg of reinforcing fiber, and 2 kg of water reducer; the reinforcing fiber used is prepared in the reinforcing fiber preparation example 1; the recycled coarse aggregate used is composed of concrete waste and brick waste, and the particle size is 25 mm; the recycled fine aggregate used is composed of concrete waste and brick waste, and the particle size is 10 mm; the water reducer used is maleic anhydride polyoxyethylene ester sulfonate;
[0048] The preparation process of high-strength recycled aggregate concrete in this embodiment mainly includes the following steps:
[0049] S1: Mixing the above weights of cement, recycled coarse aggregate, recycled fine aggregate, fly ash, reinforcing fiber and water reducing agent to prepare a premix;
[0050] S2: Mix the above weight of water with the premix, let stand for 30 minutes, and prepare a premixed mortar;
[0051] S3: solidify and cure the premixed mortar prepared in step S2.
[0052] Example 2
[0053] The preparation process of the high-strength recycled aggregate concrete in this embodiment is different from that in Example 1 in that the high-strength recycled aggregate concrete mainly includes the following raw materials by weight: 100 kg of cement, 60 kg of recycled coarse aggregate, 50 kg of recycled fine aggregate, 30 kg of fly ash, 130 kg of water, 20 kg of reinforcing fiber, and 3 kg of water reducer.
[0054] Example 3
[0055] The preparation process of the high-strength recycled aggregate concrete in this embodiment is different from that in Example 1 in that the high-strength recycled aggregate concrete mainly includes the following raw materials by weight: 80 kg of cement, 55 g of recycled coarse aggregate, 40 kg of recycled fine aggregate, 25 kg of fly ash, 100 kg of water, 15 kg of reinforcing fiber, and 2.5 kg of water reducer.
[0056] Example 4
[0057] The preparation process of the high-strength recycled aggregate concrete in this embodiment is different from that in Example 3 in that the reinforcing fiber used in step S1 is prepared in Reinforcing Fiber Preparation Example 2.
[0058] Example 5
[0059] The preparation process of the high-strength recycled aggregate concrete in this embodiment is different from that in Example 3 in that the reinforcing fiber used in step S1 is prepared in Reinforcing Fiber Preparation Example 3.
[0060] Example 6
[0061] The preparation process of the high-strength recycled aggregate concrete in this embodiment is different from that in Example 3 in that the reinforcing fiber used in step S1 is prepared in Reinforcing Fiber Preparation Example 4.
[0062] Example 7
[0063] The preparation process of the high-strength recycled aggregate concrete in this embodiment is different from that in Example 3 in that the reinforcing fiber used in step S1 is prepared in Reinforcing Fiber Preparation Example 5.
[0064] Example 8
[0065] The preparation process of the high-strength recycled aggregate concrete in this embodiment is different from that in Example 7 in that, before mixing the premix with water in step S2, a filler is added to the premix; the filler used is prepared by mixing styrene-butadiene rubber powder and a silane coupling agent in a mass ratio of 9:0.3; and the silane coupling agent used is γ-glycidyloxypropyltrimethoxysilane.
[0066] Example 9
[0067] The preparation process of the high-strength recycled aggregate concrete in this embodiment is different from that in Embodiment 7 in that the filler used in step S2 is composed of styrene-butadiene rubber powder and silane coupling agent in a mass ratio of 13:0.2.
[0068] Example 10
[0069] The preparation process of the high-strength recycled aggregate concrete in this embodiment is different from that in Embodiment 7 in that the filler used in step S2 is composed of styrene-butadiene rubber powder and silane coupling agent in a mass ratio of 10:0.25.
[0070] Embodiment 11
[0071] The preparation process of the high-strength recycled aggregate concrete in this embodiment is different from that in Embodiment 10 in that the filler used in step S2 is composed of glass fiber and silane coupling agent in a mass ratio of 10:0.25.
[0072] Example 12
[0073] The preparation process of the high-strength recycled aggregate concrete in this embodiment is different from that in Embodiment 10 in that the filler used in step S2 is composed of styrene-butadiene rubber powder, glass fiber and silane coupling agent in a mass ratio of 5.5:4.5:0.25.
[0074] Embodiment 13
[0075] The preparation process of high-strength recycled aggregate concrete in this embodiment is different from that in Embodiment 12 in that, before the premixed slurry is solidified in step S3, 6 kg of epoxy resin is added to the premixed slurry; the epoxy resin used is bisphenol A epoxy resin.
[0076] Comparative Example
[0077] Comparative Example 1
[0078] The preparation process of the high-strength recycled aggregate concrete in this comparative example is different from that in Example 1 in that the reinforcing fiber used is steel fiber.
[0079] Comparative Example 2
[0080] The preparation process of the high-strength recycled aggregate concrete in this comparative example is different from that in Example 1 in that the preparation method of the reinforcing fiber in this preparation example comprises the following steps:
[0081] Take a reaction bottle, add polyamide 66 and polymethacrylate into the reaction bottle, heat the reaction bottle at 280°C to melt the polyamide 66 and polymethacrylate, and then evenly mix them with calcium chloride to prepare a coating liquid; apply the coating liquid on the surface of the steel fiber, take it out, and dry it; the mass ratio of calcium chloride, polymethacrylate and polyamide 66 used is 1:2:13; the steel fiber used is composed of long fiber and short fiber in a mass ratio of 4:2.5; the length of the long fiber is 40 mm, and the length of the short fiber is 20 mm.
[0082] Comparative Example 3
[0083] The preparation process of the high-strength recycled aggregate concrete in this comparative example is different from that in Example 1 in that the preparation method of the reinforcing fiber in this preparation example comprises the following steps:
[0084] Take a reaction bottle, add polyamide 66 and polymethacrylate into the reaction bottle, heat the reaction bottle at 280° C. to melt polyamide 66 and polymethacrylate to prepare a coating liquid; apply the coating liquid on the surface of the steel fiber, take it out, and dry it to prepare a pretreated fiber; the mass ratio of polymethacrylate to polyamide 66 is 2:13; the steel fiber is composed of long fiber and short fiber in a mass ratio of 4:2.5; the length of the long fiber is 40 mm, and the length of the short fiber is 20 mm;
[0085] S12: Take an immersion bucket, add acetone solution into the immersion bucket, immerse the pretreated fiber in the acetone solution for 20 minutes, take out and dry.
[0086] Comparative Example 4
[0087] The preparation process of the high-strength recycled aggregate concrete in this comparative example is different from that in Example 1 in that the preparation method of the reinforcing fiber in this preparation example comprises the following steps:
[0088] Take a reaction bottle, add polyamide 66 into the reaction bottle, heat the reaction bottle at 280° C. to melt the polyamide 66, and then evenly mix it with calcium chloride to prepare a coating liquid; apply the coating liquid on the surface of the steel fiber, take it out, and prepare the pretreated fiber; the mass ratio of calcium chloride to polyamide 66 is 1:13; the steel fiber is composed of long fiber and short fiber in a mass ratio of 4:2.5; the length of the long fiber is 40 mm, and the length of the short fiber is 20 mm;
[0089] S12: Take an immersion bucket, add acetone solution into the immersion bucket, immerse the pretreated fiber in the acetone solution for 20 minutes, take out and dry.
[0090] Detection Methods
[0091] Recycled aggregate concrete was prepared according to the preparation process of high-strength recycled aggregate concrete in Examples 1-13 and Comparative Examples 1-4, and the recycled aggregate concrete was prepared into cubic test blocks with a size of 15 cm*10 cm*20 cm. After curing and curing, it was placed for 30 days as experimental samples. The compressive strength of the experimental samples was tested according to GBT50107-2010 "Concrete Strength Test and Evaluation Standard", and the data were recorded to obtain Table 1:
[0092] Table 1 Compressive strength of recycled aggregate concrete prepared in Examples 1-13 and Comparative Examples 1-4
[0093] Serial number Compressive strength(MPa) Example 1 23.1 Example 2 23.4 Example 3 23.9 Example 4 24.0 Example 5 24.8 Example 6 25.1 Example 7 25.6 Example 8 26.2 Example 9 26.4 Example 10 26.9 Embodiment 11 26.7 Example 12 27.5 Embodiment 13 28.6 Comparative Example 1 15.9 Comparative Example 2 16.6 Comparative Example 3 17.9 Comparative Example 3 18.5
[0094] Combining Examples 1-7, Comparative Examples 1-4 and Table 1, it can be seen that by adjusting the ratio between the various raw materials in the concrete and adding reinforcing fibers inside the concrete, in the preparation process of the reinforcing fibers, the mass ratio of calcium chloride, polymethacrylate and polyamide 66 is adjusted, the three together form a coating liquid, and the coating liquid is wrapped on the surface of the steel fiber, which has a good protective effect on the steel fiber after drying. By comparing the data of Examples 3-5, it can be seen that by combining long fibers and short fibers, the compressive strength of the prepared concrete can be better improved; at the same time, compared with Comparative Example 1, the coating liquid can slow down the corrosion and rusting rate of the steel fiber and improve the mechanical properties of the steel fiber when used for a long time; compared with Comparative Example 2, and by acetone The impregnation effect of the solution dissolves the calcium chloride and polymethacrylate on the surface of the coating layer, making the surface of the coating layer rough, increasing the firmness of the prepared reinforcing fiber fixed in the concrete, and thus improving the compressive strength of the prepared concrete; by comparing with comparative examples 3-4, since the calcium chloride is embedded in the surface of the coating layer after the coating layer is dried, the acetone solution dissolves the calcium chloride to form pores on the surface of the coating layer, and other raw materials of the concrete enter the pores to form a "rivet" structure, combined with the rough effect of the coating layer surface after the polymethacrylate is dissolved, the combination of the two further improves the stability of the reinforcing fiber in the concrete, making it difficult for the reinforcing fiber to move when the concrete is subjected to external force, and having a good mechanical property enhancement effect on the concrete;
[0095] It can be seen from Examples 8-12 and Table 1 that when the filler is composed of styrene-butadiene rubber powder, glass fiber and silane coupling agent in a mass ratio of 5.5:4.5:0.25, after the styrene-butadiene rubber powder is added to the concrete, it can be mixed with the silane coupling agent, so that the methoxy group in the styrene-butadiene rubber is hydrolyzed to produce silanol, thereby improving the dispersibility of the styrene-butadiene rubber and the filling and toughening effect of the styrene-butadiene rubber on the concrete; at the same time, the glass fiber is compounded, and when the glass fiber is mixed with the silane coupling agent, the epoxy functional group on the silane coupling agent is ring-opened and combined with the hydroxyl group on the surface of the glass fiber, and the polyamide 66 has a large number of amino groups, terminal carboxyl groups and amide bonds, so that the silane coupling agent can be bonded with the polyamide 66 after mixing with the glass fiber to form a bonding force; with the cooperation of the styrene-butadiene rubber powder, the glass fiber and the silane coupling agent, the internal structure of the prepared concrete is more compact and the compressive strength is better;
[0096] It can be seen from Example 13 and Table 1 that by adding epoxy resin as a reinforcing agent to the raw materials for preparing concrete, the epoxy resin is cross-linked to form a network structure during the mixing process of concrete, and at the same time, physical adsorption and chemical bonding occur with the amino group and amide bond in polyamide 66. Under the combination of polyamide 66 and epoxy resin, the reinforcing fibers are driven to be interspersed and fixed in the network structure. When the concrete is subjected to external force, the external force is transmitted to the network structure through the reinforcing fibers. Under the dispersing effect of the network structure, the stress is dispersed to the interior of the concrete, thereby reducing the phenomenon of concrete cracking caused by stress concentration inside the concrete, and further improving the reinforcing effect of the reinforcing fibers on the mechanical properties of the concrete.
[0097] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A high-strength recycled aggregate concrete, characterized in that: The raw materials mainly include the following parts by weight: 70-100 parts of cement, 50-60 parts of recycled coarse aggregate, 30-50 parts of recycled fine aggregate, 20-30 parts of fly ash, 80-130 parts of water, 10-20 parts of reinforcing fiber, and 2-3 parts of water reducing agent; the preparation method of the reinforcing fiber includes the following steps: S11: heating and melting polyamide 66 and polymethacrylate and mixing them with calcium chloride to obtain a coating liquid, applying the coating liquid on the surface of the steel fiber, and drying to obtain a pretreated fiber; S12: The pretreated fiber prepared in step S11 is immersed in an acetone solution, and then taken out and dried.
2. The high-strength recycled aggregate concrete according to claim 1, characterized in that: When the pretreated fiber is immersed in the acetone solution, the acetone solution is simultaneously subjected to ultrasonic treatment.
3. The high-strength recycled aggregate concrete according to claim 1, characterized in that: In step S11, the steel fiber is immersed in a zinc phosphate solution before use, and then taken out and dried.
4. The high-strength recycled aggregate concrete according to claim 3, characterized in that: The steel fibers are composed of long fibers and short fibers in a mass ratio of (3-5):(2-3); the length of the long fibers is 35-45 mm, and the length of the short fibers is 15-25 mm.
5. The high-strength recycled aggregate concrete according to claim 1, characterized in that: The mass ratio of calcium chloride, polymethacrylate and polyamide 66 in step S11 is 1:(2-4):(13-18).
6. A process for preparing high-strength recycled aggregate concrete according to claim 1, characterized in that: The main steps are as follows: S1: Mix cement, recycled coarse aggregate, recycled fine aggregate, fly ash, reinforcing fiber and water reducing agent to prepare a premix; S2: Mixing water and premix, and letting them stand to prepare premixed mortar; S3: solidify and cure the premixed mortar prepared in step S2.
7. The process for preparing high-strength recycled aggregate concrete according to claim 6, characterized in that: Before mixing the premix with water in step S2, a filler is added to the premix, and the filler is composed of at least one of styrene-butadiene rubber powder and glass fiber and a silane coupling agent in a mass ratio of (9-13): (0.2-0.3).
8. The process for preparing high-strength recycled aggregate concrete according to claim 7, characterized in that: The filler is composed of styrene-butadiene rubber powder, glass fiber and silane coupling agent in a mass ratio of (5-8):(4-5):(0.2-0.3).
9. The process for preparing high-strength recycled aggregate concrete according to claim 8, characterized in that: 5-8 parts of epoxy resin are added to the premixed mortar before curing.
Citation Information
Patent Citations
Corrosion protection method of steel fibers
CN103787603A
Ultra-high performance concrete based on steel fiber surface modification and preparation method
CN115477516A